Does cue processing modulate inhibition of return in a detection task?. Issue 1 (29th October 2018) - Zhou, Bin; Yang, Taoxi; Bao, Yan
Abstract: While the abrupt onset of a peripheral visual cue usually leads to speeded responses to following targets at the cued relative to other positions, responses are slowed if targets lag behind the cue by more than 200 ms. This response delay is termed inhibition of return (IOR) and has been considered as a mechanism to orient behavior toward novel areas. IOR has been found in both detection and discrimination tasks with later onset in discrimination tasks, probably due to a higher processing demand. Here we examined whether the processing demand of cues can modulate IOR in the detection task. The task to the peripheral cues, either color or gap cues, was passive viewing in one session (single task) and discrimination in another session (dual task). The results showed that the time course of IOR was resistant to the cue processing, while the magnitude of IOR was increased when the processing load became larger in the dual task relative to the single task. These results indicate that IOR in target detection is both reflexive in that its temporal dynamics remain invariant, and flexible in that its magnitude is modulated by task requirement.